ANALISIS PERHITUNGAN ULANG LAMPU PENERANGAN JALAN BYPASS NGURAH RAI - Gede Andre Agusta Putra; I Ketut Wijaya; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2020)
Public Street Lighting is a facility needed as a navigation aid for road users, increasingthe safety and comfort of road users, and supporting environmental security. The lack of lightingon the Ngurah Rai Bypass road is then performed a recalculation analysis and replacing theexisting lamps with LED types in order to maximize the lighting contained in the Ngurah RaiBypass. Measurements are made starting from the intersection of the Bali Mandara Toll roadtraffic lights towards (East) Sanur which ends at the first traffic light after the Bali Mandara Tolltraffic light, this road is an Arterial type road with a road width of 8 meters with a road length of1270m. The method used in this research is descriptive quantitative, that is, data collection isdone through measurement using objective and standard tools. The calculation results are thencompared with the conditions that occur in the field using IBM SPSS Statistics. Based on theresults of the research, it shows that the lamps installed with 10.21 lux still do not meet SNI 11-20 lux. Changing the type of mercury lamp to a 120 Watt LED lamp produces 13.21 lux, whichmeets SNI for PJU lighting.